Enlargement of the European Union and security of the Baltic states - Gricius, Algirdas (Politologija, 1997)
In the article, the author notes that issues of security and stability seem to be the most difficult to solve throughout the history of international relations. While examining the problems of external security of the Baltic states, it is necessary to take into account not only the search for their solution within the framework of relations with the neighboring states, European and Euro-Atlantic organizations, but also the impact of decisions made by the above-mentioned organizations on the internal security of these states. In the analysis of the outcomes of the NATO Madrid Summit, which decided to enlarge the Alliance, a comparison of two studies about the possibility of the Baltic States to join NATO, performed by the Atlantic Council and Rand Corporation, is presented. It is shown that there are different approaches on how to provide security for the Baltic States and stability in the Baltic region. It is stressed that the Summit of heads of NATO states in Madrid lacked determination to name clearly the Baltic States as future members of NATO. Nevertheless, it is possible to notice some positive points in the Madrid declaration. In this document, the Baltic States are presented as the states of the Baltic region that are seeking NATO membership. The US State Secretary Ms. Madeleine Albright’s remark, made during her visit to Vilnius after the Madrid Summit that new NATO members must not only be security consumers, ought to be perceived as a suggestion that, before becoming full-fledged members, the Baltic States still have much to do in the sphere of defense at home. Analyzing the outcomes of the Intergovernmental Conference which was concluded in Amsterdam, one can state that solutions on many issues, which were discussed during the conference, can be considered as partial, except those which enabled to complete the works envisaged in the Maastricht Agreement. The article presents different evaluations of the progress in coordination of joint foreign and security policy of the European Union. Commission’s avis on Lithuania and other Baltic states’ application for membership of the European Union and its influence on further political development in the above-mentioned states are discussed in the article, as well as the Lithuanian Government’s position on the Commission’s opinion. Pointing out the enormous work performed by the Commission and agreeing with the majority of assessments concerning the progress achieved by Lithuania in meeting the Copenhagen Council criteria for future membership, the Lithuanian Government, however, cannot agree with the final conclusion that Lithuania does not yet meet the requirements to start accession negotiations. The article also discusses Lithuanian strategy and the conduct of the states, which were not qualified by the Commission to start negotiations in 1998, during the second half of 1997, till the Luxembourg Council. It is mentioned that one can anticipate rather intensive lobbying activities by them in the Union member states. One can like it or not, but integration into the European Union is an individual race or even contest and all applicant countries are involved in it. In this context, the narrow possibility to enhance the Baltic States’ cooperation is also discussed. The Baltic States’ security issues are discussed to the extent relevant to the EU enlargement. It is stated that the European Union would not stay aside in case the independence of the Baltic States is endangered. However, the Baltic States strive for long-term security and stability in the Baltic region, which could prevent any possibility of danger to their independence. All states which are aspiring to the European Union membership, apparently, have the same objectives: first, to consolidate their democracy, second, to enhance their well-being, and third, to increase their security. Expectations of the European Union from the new members can also be presented along the same lines: spread of democracy, expansion of the market and possibilities for investments, enhancement of security, and avoidance of economic and social instability. The comparison of these two objectives allows drawing a conclusion that the European Union will have fewer problems related to the above-mentioned issues by allowing new members to join the Union rather than leaving them outside. Today and perhaps in the nearest future, no real threat exists for the security and independence of the Baltic States. But in the longer-term perspective, no one can claim that such danger will not arise to some European and the Baltic states. One of the means of minimizing such a possibility is the European Union or, at least, the start of accession negotiations. In concluding thoughts, it is stated: first, membership of the European Union or a successful start of accession negotiations would broaden political and economic relations with the EU Member States, second, broader political and economic relations with Western countries or even more full-fledged membership of the Union should provide the so-called soft security guarantees, and third, more successful economic development would allow the Baltic States to allocate more financial resources for social and defense purposes, which in its own turn would enhance the internal security and enhance the possibility to join NATO in the future.